Effect of Atmosphere on Crystallisation Kinetics and Phase Relations in Electrospun TiO2 Nanofibres - Albetran, Hani Manssor Mohammed; Haroosh, Hazim Jasim Mohammed; Dong, Yu; O'Connor, B.; Low, It Meng (John Wiley & Sons, Inc, 2014)
Titanium dioxide has received much attention as an important photocatalytic material. In this paper, the effects of air and argon atmosphere on the crystallisation kinetics and phase relations in electrospun TiO2 nanofibres have been investigated using high- temperature synchrotron radiation diffraction. Diffraction results showed that as-synthesized TiO2 was amorphous initially, but when heated in air or argon atmosphere they crystallized to form anatase and rutile at different temperatures and indifferent rates. The crystallisation of anatase was delayed by 100 °C in argon when compared to in air. However, the transform rate of anatase to rutile was faster in argon than in air.